Dietary fibre-rich oyster mushroom (pleurotus sajor-caju) powder as food ingredient and its application in developing low-glycaemic biscuit - Han, Ng Sze (2017)
Consumer’s demand for functional food is increasing due to high prevalence of non communicable diseases. Grey oyster mushroom (Pleurotus sajor-caju, PSC) which cultivated widely in Malaysia possesses various medicinal properties but lack of attention on its diabetes-related physiological function and its application in functional food development. Hence, this study aimed to determine the nutritional values, functional properties, storage stability, in vitro and in vivo hypoglycaemic effects of PSC powder as well as its application in developing low-glycaemic index (low-GI) biscuit. The effects of PSC powder as wheat flour replacer (0, 4, 8 and 12%) in biscuit on nutritional, physicochemical, textural and sensorial properties as well as GI were examined. Results showed that PSC powder contained appreciable amounts of protein (22.41%), ash (7.79%), dietary fibre (DF) (56.99%) and β-glucan (3.32%) but negligible amounts of sucrose (0.19%) and fat (2.30%). It also featured water holding capacity (13.46 g/g), oil holding capacity (8.52 ml/g), swelling capacity (19.49 ml/g) and emulsifying activity (51.67%). Storage study revealed that PSC powder exhibited significant lower L* colorimetric value meanwhile microbial counts remained unchanged with increasing storage temperature and duration. The mechanisms of PSC powder to elicit the in vitro hypoglycaemic effects were through glucose adsorption, retardation of glucose diffusion across dialysis membrane and delayed glucose release from starch by inhibition of α-amylase activity. The hypoglycaemic potentials of PSCpowder were higher than oat, barley and atta flour. In addition, PSC aqueous extract (PSCE) demonstrated significant blood glucose (BG) reduction and glucose tolerance improvement in normal and streptozotocin (STZ)-induced diabetic rats. The PSCE at 750 mg/kg was identified as the optimum effective dose and its effects were comparable to metformin (150 mg/kg). In 21-days study, BG, body weight and urine sugar in PSCEtreated diabetic rats were reported significant improvement compared to control diabetic rats. PSC powder incorporation in biscuit resulted in increased nutritional values particularly DF, disturbed structure and reduced diameter of starch granules, reduced pasting viscosity, reduced enthalpy of starch gelatinisation, increased proportion of slowly digestible starch and eventually reduced GI of biscuit. The addition of 8% PSC powder is the best formulation in developing low-GI (GI=49), high TDF (8.62%) and well-accepted functional biscuit. Therefore, PSC powder can be used as a food ingredient and in development of low-GI biscuit.